The glassblower of Murano (St. Martin's Publishing Group, St. Martin's Griffin, 2009)
Venice, 1681. Glassblowing is the lifeblood of the Republic, and Venetian mirrors are more precious than gold. Jealously guarded by the murderous Council of Ten, the glassblowers of Murano are virtually imprisoned on their island in the lagoon. But the greatest of the artists, Corradino Manin, sells his methods and his soul to Louis XIV of France to protect his secret daughter. In the present day, his descendant, Leonara Manin, leaves London for a new life as a glassblower in Venice -- only to find her fate inextricably linked with her ancestor's dangerous secrets--Cover.